Determinants of Financial Performance of Sharia Commercial Banks With Capital Adequacy Ratio and Sharia Supervisory Board as Moderator Variables - Burhanuddin, Burhanuddin; Marsoem, Bambang Santoso (Green Publisher Indonesia, 2024)
This study aims to determine and examine the effect of Capital Adequency Ratio, Non-performing Financing (NPF), Islamic Corporate Social Resposibility (ICSR), Financing to Deficit Ratio on Financial Performance and Sharia Supervisory Board as Moderator variables. This study used a type of quantitative descriptive research. The population in this study is 13 sharia Commercial Banks in Indonesia and the sampling technique used is purposive sampling, there are 10 Sharia Commercial Banks that have criteria as research samples. In this study, the data analysis methods used are Descriptive Statistical Analysis, Multiple Linear Regression, Classical Assumption Test, Hypothesis Test and Model Moderated Regression Analysis (MRA) Test. The results showed that Akad Mudharabah and Musyarakah Financing did not have a significant effect on financial performance, Non-performing Financing (NPF) did not affect financial performance, Islamic Corporate Social Resposibility (ICSR) had a positive and significant effect on financial performance, Financing to Deficit Ratio does not have a significant effect on Financial Performance. The results showed that the CAR moderator variable could only moderate the ICSR against ROA. Furthermore, for variables DPS moderators can only moderate Akad Mudharabah and Musyarakah Financing against ROA and moderate ICSR against ROA.